Marketing - Charles W. Lamb (Oxford University Press, 2004)
Marketers must be fully equipped to meet the challenges of the information and technology driven marketplace in South Africa. Marketing 2/e helps students to turn information into useful knowledge, to obtain the competitive advantage and to be successful in the marketplace. The South African examples and comment in an international setting creates local and global perspectives. The text works at a small business entrepreneurial level and provides appropriate material for work in small teams. The text also examines marketing from a global perspective. The organization of the text is OBE and modularized. Thus, it has a fully integrated learning system. The expanded strategy component and a balance of theory and practice makes the text suitable for universities and technicons.